Problemáticas epistemológicas en la planificación de la enseñanza del Derecho - Mosquera Schvartz, David Manuel (2015)
This arcticle explains briefly the epistemological problems that teachers faces in the planning of Law education. These problems affect directly the whole teaching process. Some problems are related to the construction of the content, while others are related to the difficulties of transforming a disciplinary content into a college textbook. In all cases teachers must overcome these difficulties and they also need to develop a didactic strategy to handle the task of teaching all to everybody successfully.